Epilepsy in the emergency department: Who needs hospitalization? (Annals of Medical Research, 2021)
Aim: Epilepsy is one of the most common serious chronic neurological diseases, imposing a huge economic burden on the individual and the society. Hospital services have been shown to be the highest direct-cost source for epilepsy patients. Therefore, in our study, we planned to discern the indications of hospitalization and the factors affecting the decision to hospitalize.Material and Methods: Patients admitted to our adult emergency department with epileptic seizures were included in the study between February 2017 and September 2018. A total of 111 patients were recorded in terms of demographic data, preferred transportation method when arriving at the emergency department, anti-epileptic drugs they used, seizure triggers, pre-hospital treatments, duration of seizures, and indication, and duration of hospitalization. Results: The rate of status epilepticus was lower in patients receiving a single antiepileptic drug compared to patients receiving two antiepileptic drugs and those using three or more antiepileptic drugs. The duration of the hospital stay was longer in patients receiving three or more antiepileptic drugs. Single antiepileptic drug users had a lower rate of hospitalization and a lower rate of intensive care unit admission and pre-hospital ambulance medication. Conclusion: The most significant variable affecting the study’s results was the number of antiepileptic drugs used by the patients. Patients receiving polytherapy should be considered as a special group, and the effects of this situation on both the individual and the health care system should be examined in more detail.
Keywords: Hospitalization; status epilepticus; status epilepticus in emergency department